Value of confocal laser endomicroscopy in the diagnosis of vocal cord lesions - Goncalves, M.; Iro, Heinrich; Dittberner, A.; Agaimy, Abbas; Bohr, Christopher (European Review for Medical and Pharmacological Sciences, 2017)
The aim of this study was to assess the reliability and limitations of confocal laser endomicroscopy (CLE) for diagnosing lesions of the vocal cords and differentiating malignant from non-malignant lesions.During microlaryngoscopy, the vocal cords were scanned by probe-based CLE (pCLE: a GastroFlex probe with the Cellvizio® laser system, Mauna Technologies, Paris, France). The video recordings were analyzed and compared with the histological results. Thirty-one representative images were extracted and presented to four medical professionals (blinded examiners) for assessment.The accuracy for the category malignant/nonmalignant ranged between 58.1% and 87.1%. Overall interrater reliability was 0.29. Sensitivity ranged between 45.5 and 100%, specificity between 60.0 and 100%, PPV between 38.5% and 100% and NPV between 66.7 and 100%.CLE is a promising method for the non-invasive diagnosis of vocal cord lesions in vivo, but factors such as small penetration depth, not available contrast media for the nuclei and subjective analyses of the images limit, at the moment, its diagnostic value.
EVALuna2:6891